Microsimulation of life-stage transitions and residential location transitions within a life-oriented integrated urban modeling system. (May 2018) - Fatmi, Mahmudur Rahman; Habib, Muhammad Ahsanul
Abstract: This paper presents microsimulation of life-stage transitions and residential location transition processes within a life-oriented agent-based integrated Transport Land Use and Energy (iTLE) modeling system. The iTLE assumes that individuals and households are the agents, and parcels are the objects. It is conceptualized following the life-course perspectives and theories to address the evolution of multi-domain decision interactions over the life-course of the agents. Residential location is simulated as a two-stage process of residential mobility, and location choice. Life-stage simulation includes aging, death, birth, out-migration, in-migration, and household formation. The iTLE is implemented at a yearly time-step from 2006 to 2021 for Halifax, Canada. A 100% synthetic population is generated for the base year 2006, which shows a SRMSE value of 0.37 and APE measures of less than 5% for 89% of the DAs. The simulation results are validated with the 2011 Census information. The validation results suggest that the iTLE generates reasonably satisfactory population estimates. For example, around 52% of the DAs show an APE value of less than 30%, and 37% of the DAs show a difference in the number of households of less than ±50. The predicted results regarding the spatio-temporal evolution of Halifax suggests an increase of around 14% population in 2021 compared to 2007. Younger population residing closer to the CBD are predicted to be more frequent movers than older population residing farther away from the CBD. Higher proportions of the households are predicted in the locations within 25 km from the CBD over the years. Proportion of households in these high density neighborhoods are predicted to increase from 68% in 2007 to 71% in 2021. In 2021, a higher density of single person households are predicted in the urban core. Density is predicted to be more variable and skewed towards suburban neighborhoods as household composition changes through marriage and child birth. Highlights: Microsimulates life-stages and residential locations within a life-oriented agent-based urban system simulation platform Addresses multi-way decision interactions over the life-course of the agents Residential location decision is simulated as a two-stage process of mobility and location choice 15-year simulation results suggest that 71% households reside in high density areas in 2021 compared to 68% in 2007 Predicts a skewed density of couple, and couple with children households in suburban areas than single person households